2021
DOI: 10.1177/16094069211016719
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Educational and Environmental Awareness Outcomes Through Photovoice

Abstract: In the United States, there are substantial barriers to youth nature access and environmental education (EE). These barriers may lead to racial, geographic, and socioeconomic disparities in both nature contact and environmental awareness. This study investigated the impacts of a Photovoice EE intervention on the environmental perceptions, STEM-capacity, and environmental awareness of 335 low-income, urban youth (ages 9–15). Youth were assigned to one of two intervention groups, a Photovoice EE intervention gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 56 publications
(80 reference statements)
2
14
0
Order By: Relevance
“…This results supported by the result of the Trott (2019) study, who concluded that participants reported increased engagement in personal pro-environmental behaviors in climate change after implementation of SCA program. Also, the current study was in line with the study of Sprague et al (2021) who observed that students associated the environment with social interactions as well as outdoor experiences with peers and family members and the photovoice intervention improved youths' social and familial functioning. Improvement in knowledge, attitude and daily life practices of school age children after the implementation of climate change photovoice program in the present study can be justified as the program was built on their interest and enjoyment regarding CC, which help them in modifying their behaviors towards environmental activities and enhancing their cooperation and teamwork.…”
Section: Discussionsupporting
confidence: 89%
“…This results supported by the result of the Trott (2019) study, who concluded that participants reported increased engagement in personal pro-environmental behaviors in climate change after implementation of SCA program. Also, the current study was in line with the study of Sprague et al (2021) who observed that students associated the environment with social interactions as well as outdoor experiences with peers and family members and the photovoice intervention improved youths' social and familial functioning. Improvement in knowledge, attitude and daily life practices of school age children after the implementation of climate change photovoice program in the present study can be justified as the program was built on their interest and enjoyment regarding CC, which help them in modifying their behaviors towards environmental activities and enhancing their cooperation and teamwork.…”
Section: Discussionsupporting
confidence: 89%
“…Photovoice has been used to engage youth in a range of environmental and conservation efforts (Bulla & Steelman, 2016;Derr & Simmons, 2020;Trott, 2019) and has been shown to improve both learning outcomes and sense of agency in environmental education (Sprague et al, 2021). Cook (2014), for instance, found that the use of photovoice improved undergraduate students' learning of scientific concepts and increased interest in local environmental issues.…”
Section: Photovoicementioning
confidence: 99%
“…One of our key takeaways was the importance of educating community partners. Community science has been recognized as a powerful tool to educate and inform the non-scientific community (de Sherbinin et al, 2021;Herodotou, 2018;Sprague et al, 2021). The challenge is finding the right approach.…”
Section: Lessons Learned/community Feedbackmentioning
confidence: 99%